Decline in Self‐reported Health (EQ‐5D) over Time after Surgical Reconstruction of the Right Ventricular Outflow Tract: A Longitudinal Cohort Study of 103 Patients. (17th August 2014) - Skoglund, Kristofer; Berghammer, Malin; Eriksson, Peter; Svensson, Gunnar; Thilén, Ulf; Dellborg, Mikael
Abstract Objective Patients with congenital heart disease may be operated with surgical reconstruction of the right ventricular outflow tract (RVOT). Reintervention is common in this group of patients. The aim of this study was to examine longitudinal self‐reported health measured by the EQ‐5D questionnaire. Design Data were collected from the Swedish Registry of Congenital Heart Disease. EQ‐5D, which measures health outcome, was introduced into the registry in 2005. All adult patients with previous surgical reconstruction of the RVOT who had EQ‐5D data from their first and latest visit were analyzed. Results Among 103 patients (65 male and 38 female), mean age 31 (range 19–78 years), the diagnoses were: tetralogy of Fallot (n = 66); truncus, transpositions, and double outlet right ventricle (n = 23); and Ross‐operated congenital aortic valve disease (n = 14). Time from first to latest visit was 3 years (range 1–7 years). Eighteen patients underwent 26 reinterventions in the observational period from the first to latest visit, including operations, percutaneous interventions, pacemaker implantations, and ablations. Health perception, mean EQ‐5D visual analog scale, VAS, declined from 84.4 (standard deviation (SD) = 14.6) to 78.6 (SD = 18.3) at the latest visit, P = .001. The decline is almost exclusively seen in patients without reinterventions. Low EQ‐VAS was associated with symptoms and New York Heart Association class II–IV. Patient‐reported problems in the EQ‐5D dimension usual activities were more common in the patients having reinterventions (25%) than those without reintervention (7%), P = .04. Conclusion In this longitudinal cohort study of patients with previous surgical reconstruction of the RVOT, health perception declined over time. The decline was not observed in patients undergoing any additional interventions.